THE IMPACT OF WORK STRESS AND WORK MOTIVATION ON JOB SATISFACTION AND ITS IMPLICATIONS ON NURSES' PERFORMANCE - Sisilia Sudargo; Soegeng Wahyoedi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The quality of healthcare services is one of the key factors in the success of health systems across countries. The professionalism of nurses in hospitals plays a crucial role in the delivery of healthcare services. Hospitals are often high-pressure work environments that require nurses to operate in dynamic and uncertain conditions. In such challenging settings, numerous factors affect nurse performance, one of which is job stress. Job stress refers to a pattern of emotional conditions that arise in response to demands from within or outside the organization. This study aims to analyze the influence of job stress and work motivation on job satisfaction, and their implications for nurse performance. The sampling method used in this study is probability sampling. The total population at Sumber Waras Hospital consists of 241 nurses, including 42 outpatient nurses, 69 inpatient nurses, 22 dialysis nurses, 33 operating room nurses, 55 intensive care nurses, and 20 emergency nurses. Therefore, the sample used in this study comprises 69 inpatient nurses. The results of the study indicate that job stress has a significant effect on job satisfaction, meaning that higher levels of job stress tend to decrease job satisfaction. Work motivation significantly affects job satisfaction, indicating that higher motivation among inpatient nurses increases their job satisfaction. Furthermore, job satisfaction has a significant influence on nurse performance, showing that nurses who are satisfied with their jobs tend to perform better.